Quakers in Northeast Norfolk, England, 1690-1800 - Stevens, Sylvia, 1935- (Lewiston : Edwin Mellen Press, 2012)
Some of the eighteenth-century Quakers in northeast Norfolk were well-known among Quakers nationally in their time. Others were known regionally, and locally, leaving few printed records of their experiences. This book argues that it is important to restore at least some of these men and women to their places in history. In order to provide a wider base from which to make reassessments about the nature of eighteenth-century Quakerism, and its religious influences, one must learn about the lesser known members. The book uses a local study to investigate the ways in which, within their local and.
Chapter 1: Introduction; Chapter 2: The Pattern of Settlement and Social Context of Quakers in Northeast Norfolk; Chapter 3: Travelling in the Service of Truth; Chapter 4: A Believing People; Chapter 5: Neighbourhood and Witness: Tensions and Resolutions; Chapter 6: Transmisson of Values and the Interests of a Polite Society; Chapter 7: Conclusion; Appendices; Appendix 1A; Appendix 1B; Appendix 1C; Appendix 2A; Appendix 2B.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Quakers -- England -- Norfolk -- History -- 17th century; Society of Friends -- England -- Norfolk -- History -- 17th century; Religion; RELIGION / Christianity / Quaker; Quakers -- England -- Norfolk -- History -- 17th century; Society of Friends -- England -- Norfolk -- History -- 17th century; Electronic books